AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDES) - Febrianti, Andi Muzdalifah; S, Masnawaty; Afiah, Nur (Jurnal Sains Riset, 2024)
This research aimed: (1) to describe accountability in the management of village funds in Polebunging Village, Bontomanai Sub-district, (2) to describe transparency in the managemnt of village funds in Polebunging Village, Bontomanai Sub-district. The variables of this research are: (1) The accountability of APBDes management in Polebunging Village, Bontomanai District, Selayar Islands Regency as measured by Permendagri Number 20/2018, and (2) Transparency of APBDes management in Polebunging Village, Bontomanai Sub-district, Selayar Islands Regency as measured by Permendagri Number 20/2018. The population of this research are all APBDes management reports and supporting documents, and the sample are report on the management of APBDES in 2022. The data were collected by interviews and documentation. The data obtained were analyzed using data condensation, data display, and conclusing drawing. The results of this research suggests that The management of the APBDes in Polebunging Village has shown good management of village funds in accordance with Permendagri No. 20/2018, which is accountable and transparent.Keywords: Accountability, Transparency, APBDes management